Potencialidades socio-organizativas para la comercialización de la leche en Quisinche Bajo. - Iguago Freire, Gil Guillermo (2023)
This project focused on the evaluation and enhancement of dairy production in Quisinche Bajo, an area that has shown challenges in its production and commercial processes. The main problem identified was the lack of modern and efficient production techniques, with socioeconomic challenges affecting the viability of dairy products in the area. Using a mixed-methodology approach, both quantitative aspects of production and the sociodemographic, educational, and income contexts of the community were examined. From the findings, a series of strategies aimed at strengthening production and commercialization were formulated, including training, promoting associativity, product diversification, and infrastructure improvements. The main results indicate a high receptivity from the community towards the implementation of these strategies, and significant potential to enhance the quality, quantity, and profitability of dairy production in Quisinche Bajo, positively impacting the area’s socioeconomic development.